Ticari bankalarda verimlilik ve etkinlik analizi. - Akdil, Betül (My University, 1993)
unknown
Keywords: Banka ve bankacılık; Bankalar ve Bankacılık; Ekonomi; Finansman ekonomisi; Ticari bankalar (Takas bank); Verimlilik